Hybrid scheme of positron source at SPARC_LAB LNF facility - Abdrachitov S. V. Sergey Vladimirovich; Bogdanov O. V. Oleg Viktorovich; Dabagov S. B.; Pivovarov Yu. L. Yuriy Leonidovich; Tukhfatullin T. A. Timur Ahatovich (2015, 2015)
Заглавие с экрана